FEATURES OF REFLECTION OF THE CONCEPT OF WEALTH IN LINGUOCULTUROLOGY - Kodirova Nozima Gulomjon kizi (Western European Studies, 2024)
This article examines the concept “Wealth” using the example of English and Russian linguistic and cultural studies. The concept “Wealth” is a sociocultural concept; it is recorded in the speech and non-speech behavior of people, is reflected in linguistic units of various types, is characterized by national specifics, and is a complex formation. The concept of “Wealth” has a multi-level structure, consisting of six levels - conceptual, subject, associative, figurative, symbolic and evaluative. The relevance of this study is determined by the need for a cognitive understanding of the concept of “Wealth” as one of the basic concepts of Russian and English cultures. Being an object of interdisciplinary research, the concept of “Wealth” has not been fully studied in linguistics.
Keywords: сoncept; linguistic; world